Studi Kritis Terhadap Sistem Perkaderan MuhammadiyahSebagai Sistem Penyiapan Kader Muhammadiyah - Furqoni, Ridwan, Dr. H. Syamsul Hidayat, M.Ag, Dr. H. Ari Anshori (2016)
Post-reformation in 1998, there is an interesting phenomenon in the body of the largest Islamic movement in Indonesia, Muhammadiyah. Among them is the migration of pilgrims from Muhammadiyah movement to another relatively new and growing lately. They are the Tarbiyah Movement (PKS), Hizb ut-Tahrir of Indonesia (HTI), Tafsir al-Quran Assembly (MTA), Salafi Movement, and so forth. There was dissatisfaction with the Muhammadiyah which made them move and follow the methodology of the new movement. In addition to these phenomena, there is also another phenomenon, namely the dual position most of the leadership in many structures of Muhammadiyah. A leader of Muhammadiyah, who served on the panel at the regional level, also served at the local level, even a district or village. With such circumstances certainly makes leadership is not running optimally. Leadership feels less progressive and tend to be comfortable in the establishment. When examined seriously, some of the circumstances have actually indicate a problem in the body of Muhammadiyah, especially in the preparation of its human resources. This then became the core of this research. The author intends to unravel: How Muhammadiyah view of the importance of human resources in moving the organization, how the system concept of Muhammadiyah perkaderan and how the effectiveness and efficiency in its process. Information about Muhammadiyah view of the importance of human resources for the organization can be seen from the historical development of Muhammadiyah perkaderan. As for the perkaderan system determined through a review of the Muhammadiyah Perkaderan system that formulated in the book of SPM. The assessment of the effectiveness and efficiency of the perkaderan system analyzed by connecting between the needs of the Muhammadiyah cadres views of the vastness of the area of interest Muhammadiyah and preaching with various activities of perkaderan arranged in SPM. In addition to the material to do the analysis, the authors also connects with the general phenomenon of social development of today's society and theories on actual educational. This study therefore included in the category of qualitative research with descriptive analytical method. After doing a reading and analysis, looking at all that Muhammadiyah indeed attach importance and give great attention to the problem of cadres . One of the seriousness is Muhammadiyah has compiled the perkaderan system and regulary continues to evaluate its implementation . The criticism in this case is that the system is arranged not been able to be implemented efficiently and at a macro scale becomes ineffective. Related to these criticisms, the authors advise to do a more radical revision of the SPM, from the revision and improvement of the vision, mission, objectives and enrichment forms of perkaderan, so that SPM feels more contextual with the needs of the times . Keywords : Muhammadiyah, Perkaderan, Sys ems